The usage of live cultured bacteria as biosensors for research of water structure changes - V. V. Lukjanitsa (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The possibility of using biosensors (live bacteria) for revealing and visualization of molecular clusters which form in fluid water was shown by the example of the effect of laser irradiation on the water structure. The transverse dimensions of these clusters were also defined.